Activation areas of social and economic development of urban settlements - Lesia Zastavetska (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The article deals with current changes taking place in urban areas of agrarian regions of Ukraine. The analysis shows that big cities today are typically generators of innovation and investment development for a specific territory whereas towns are mainly serving centers in rural areas. It reflects changes in the socio-economic development of urban settlements that occur in trans-social relations. It was proved that the narrowing of production functions has led to imbalances between the major cities’ subsystems. All cities are elements of urban skeleton of geospatial management and resettlement that is why their development influences the entire economic space ofUkraine. They need state support and efforts on the part of governments in order to use competitive advantages of cities, enhance their socio-economic development. The development of modern urban settlements must be associated not only with the increase of their area or population, but with optimal use of inner-city resources and building of the urban environment. All cities are part of the geospatial reference frame of management and resettlement, as their development depends on the development of the entire economic space ofUkraine.